2011
DOI: 10.1038/npp.2011.280
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Centric Analysis of Serum Cotinine Levels in African and European American Populations

Abstract: To date, most genetic association studies of tobacco use have been conducted in European American subjects using the phenotype of smoking quantity (cigarettes per day). However, smoking quantity is a very imprecise measure of exposure to tobacco smoke constituents. Analyses of alternate phenotypes and populations may improve our understanding of tobacco addiction genetics. Cotinine is the major metabolite of nicotine, and measuring serum cotinine levels in smokers provides a more objective measure of nicotine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Marginally higher (i.e., trend significance) addiction severity in OUD comorbidity with MetS would support this sort of an interaction regardless of the primary index event. Of note, insulin mediates the homeostatic and reward systems' cross-talk (impairment of which might underlie the chronically relapsing nature of addictive disorders) and it has been successfully tried in nicotine 116,117 and cocaine 118 addiction. It would be of interest to test whether insulin is also able to improve metabolic and reward dysfunction in patients with OUD.…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Marginally higher (i.e., trend significance) addiction severity in OUD comorbidity with MetS would support this sort of an interaction regardless of the primary index event. Of note, insulin mediates the homeostatic and reward systems' cross-talk (impairment of which might underlie the chronically relapsing nature of addictive disorders) and it has been successfully tried in nicotine 116,117 and cocaine 118 addiction. It would be of interest to test whether insulin is also able to improve metabolic and reward dysfunction in patients with OUD.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we assessed statistical power to detect a priori genetic loci of interest from an example of a large-scale (1000 s) candidate gene association scan, and an example from a locus nominated by genome-wide association scans (GWAS), with genome-wide significance (GWS) as the statistical threshold. For self-identified non-Hispanic Black current smokers, we selected rs11187065 as an example, identified in the insulin-degrading enzyme gene as the gene-centric SNP most significantly associated with serum cotinine in the Coronary Artery Risk Development in Young Adults (CARDIA) study by Hamidovic et al [ 36 ]. The influence of rs11187065 on serum cotinine was substantial with a β of −85.1 ng/ml, with mean (SE) of 236.5 (8.1) ng/ml from 365 African American smokers [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…For self-identified non-Hispanic Black current smokers, we selected rs11187065 as an example, identified in the insulin-degrading enzyme gene as the gene-centric SNP most significantly associated with serum cotinine in the Coronary Artery Risk Development in Young Adults (CARDIA) study by Hamidovic et al [ 36 ]. The influence of rs11187065 on serum cotinine was substantial with a β of −85.1 ng/ml, with mean (SE) of 236.5 (8.1) ng/ml from 365 African American smokers [ 36 ]. Mean (SD) CPD in the CARDIA sample was 10.5 (7.4), similar to that of the TES (Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Insulin‐degrading enzyme mRNA was significantly decreased in α7 KO mice, and previous rodent studies have demonstrated that functional disruption of this gene, results in hyperinsulinemia and glucose intolerance (Fakhrai‐Rad et al ; Farris et al ). Additionally, Ide mRNA expression is altered in rats following nicotine treatment (Polesskaya et al ), whereas an allele of the Ide gene is associated with plasma cotinine levels in both European and African American smokers (Hamidovic et al ). Together with the present study, these data implicate a possible role of Ide in nicotine addiction.…”
Section: Discussionmentioning
confidence: 99%